The Angel vs the Monster: Dichotomization of Identity in The Bell Jar - Rebollar Crespo, Yesica (Journal of Artistic Creation and Literary Research, 2025)
The Bell Jar by Sylvia Plath, depicts the struggle of a woman in search of her own identity and her desire to liberate from the Angel vs Monster dichotomy imposed by society. Esther Greenwood is torn between her mother, who wants her to become an Angel and her vocation as a female writer, more compatible with the Monster. As she encounters different women who represent these archetypes in New York, Betsy and Doreen, her division of the self grows prominent in her life. This paper aims to undertake an analysis on Esther’s struggle to find herself in this dichotomy and how the displacement that she suffers while failing to identify with neither of the binaries available is the main cause of her mental illness. Esther cannot be categorized as neither Angel or Monster, but still, society’s fixation on erasing women’s dichotomization of identity force her to choose between one of them. As there is no placement in society for a woman who does not complain with either one side or the other of the identity spectrum, Esther must leave the mental asylum as either a reformed Angel or a Monster in disguise in order to continue with her life, eliminating every trace of binarism in the female identity.